Treatment-Induced Neurotoxicity After Chemotherapy and Immunotherapy: Part.1 - Puac Polanco , P.; Torres , C.; Castillo , M.; ,; ,; , (Seram, 2021)
Background Information: Treatment-induced central nervous system (CNS) toxicity is a major cause of morbidity in cancer patients which can limit the course and type of treatment. Even though the CNS is relatively resistant to the toxic effects of cancer treatment by virtue of the blood-brain barrier, CSF & low proliferative rate of neurons, neurotoxicity is the second most common dose-limiting factor after myelosuppression. The purpose of this educational exhibit is to review the imaging abnormalities found during and after chemotherapy and immunotherapy. Educational Goals/Teaching Points: Side effects of oncologic therapies will be classified in a timeline fashion after initiation of therapy into acute, subacute and chronic stages. The most common drugs for oncologic treatment producing neurotoxicity will be discussed and imaging findings, behavior of changes (re/irreversibility), treatment dose, administration route and patient vulnerability will be also addressed. Key Anatomic/Physiologic Issues and Imaging Findings/Techniques: Conventional and advanced MRI sequences which provide clues and key findings will be emphasized. Imaging cases of the brain and spine will be illustrated along with the differential diagnosis and recommended imaging work-up. Conclusion: Neurologic complications of cancer treatment have become more frequent due to increased survival rates related to new/better therapies. Early and accurate diagnosis of these complications may prevent irreversible neurological injuries and differentiates treatment-related effects from cancer progression.